Social media influencer in malaysia: a review of literature and future direction / Dr. Mohamad Hafiz Rosli ... [et al.] - Rosli, Mohamad Hafiz; Jahari, Nor Azah; Md Moid, Muzairihana; Hassan, Nor Hazwani; Mohd@Abu Bakar, Farahwahida (Universiti Teknologi MARA, Kedah, 2023)
outbreak like the Pandemic Covid-19 have raised concerns about Social Media Influencers (SMI). SMI has been seen as important to complement the business and management. SMI acted as a marketing tool that utilised the social media platform. This paper aims to review past research in Malaysia related to SMI. Relevant articles were available on Google Scholar in the period between March 2020 to July 2022 and have been screened and analysed. Our review shows that research related to SMI varies in all aspects including awareness, perception, role, impact, causal analysis study and descriptive. The finding has also shown that SMI has been involved in consumer products, healthcare, automotive, advertising, fashion, tourism and hospitality and others. In conclusion, SMI is widely accepted as one of the marketing tools in various business sectors. Policymakers and businesses need to strengthen SMI in Malaysia. Legalise SMI is vital, especially in today’s digital businesses. Future study is encouraged to examine the impact of SMI on business while suggesting a sustainable business model for SMI.